Design of a Production Activity Control System for the Computer Integrated Manufacturing Enviroment - Cooke, lain Carlyle. (Cranfield University, 1990)
This thesis describes the results of research into provision of Production Activity Control (PAC) in Computer Integrated Manufacturing Systems for manufacture of discrete parts. The role and environment of PAC systems is described, against the background of development of the discrete parts manufacturing industry. Strategies and architectures for building PAC systems are reviewed, in terms of the goals of PAC systems, and the categorisation of existing design approaches. A novel design for a PAC system is presented. A model of manufacturing is described upon which the system design is based, and which defines the applicability of the proposed system. The heterarchical, data-driven system architecture is explained, and the way in which the system's design supports the various aspect of PAC functionality is described. A simple example is presented to illustrate the workings of the system as it accepts production orders and controls production. An experimental implementation of the system is described, and the results discussed. Recommendations for future implementations are'made in further discussion, stemming from the experiences of this experimentation, and from consideration of wider issues in the development of manufacturing technology. The thesis concludes with a brief statement of achiever nts, an'' some recommendations for directions of further research.